Optimization of Parameters Involved in the Transformation of Oil Palm Using the Biolistic Method - Ghulam Kadir, Ahmad Parveez (1998)
Physical and biological parameters affecting DNA delivery into oil palm embryogenic calli using the biolistic device have been optimized. The physical parameters tested were : helium pressure, distance from rupture disc to the macro carrier, distance from macro carrier to the stopping plate, distance from stopping plate to the target tissue, vacuum pressure, number of bombardments, particle types and sizes, and the effect of calcium chloride and spermidine on microcarrier-DNA binding. The optimized biological parameters were: explant types with gold micro carrier, explant types with tungsten, duration of callus culture in fresh medium prior to bombardment, duration between bombardment and GUS staining, genotype, immature embryo preculture duration, DNA concentration, osmoticum type and concentration and osmoticum treatment duration before and after bombardment. Independent experiments were carried out to study the effects of each parameter and its variables on transient expression. Two days after bombardment, the tissues were stained with GUS assay buffer for 16-20 hours at 37°C and the blue spots counted under a binocular microscope. All the variables used in these experiments were found to be significantly different except for vacuum pressure, bombardment number and genotype. The efficiency of GUS gene expression was measured in embryogenic calli and young leaves of mature and seedling palms using five constructs carrying different promoters : Emu; Ubil; Actl, 35S and Adhl were evaluated to identify the most suitable promoter for use in oil palm. The GUS gene expression from the different promoters was assayed histochemically and fluorometrically from a total of 200 plates of target tissues in eight independent experiments. Significant effects on transient GUS gene expression were demonstrated by each of the different promoters tested. The effectiveness of kanamycin; geneticin (G-418); neomycin, hygromycin and basta as selection agents to inhibit growth of oil palm embryogenic calli was evaluated. Embryogenic calli were separately exposed to all these selection agents at different concentrations ranging from 1 to 2000 mg/l for a period of one month. This was done in two replicates and repeated twice to ensure reproducibility of the selection system. Of the five compounds tested, hygromycin and basta were found to be most suitable as selection agents for oil palm as they can stop the growth of embryogenic calli at lower concentrations.Bombarded embryogenic calli were exposed to 40 or 80mg/l of selective agents after 1 or 3 weeks. It was found that there were no significant differences in the number of resistant embryogenic calli produced per plate when selected at different concentrations and time. The presence of transgenes in the resistant embryogenic calli was confirmed by PCR and Southern analysis. Transgenic embryogenic calli were later regenerated into whole plants and their transgenic status verified by PCR and Southern analysis. Problems faced during the study and their solutions are also discussed. As oil palm has a long breeding cycle, inheritance of transgenes cannot be demonstrated within the period of this study. Therefore, rice, a model crop for monocot transformation, was also used for transformation experiments. Calli derived from immature embryos were bombarded and were selected on hygromycin. Resistant calli isolated were regenerated into whole plants. Two transgenic lines were obtained. T1 and T2 from one of the clones were also produced and analysed. Integration and inheritance of the transgenes were followed by phenotypic and genotypic analysis.